Discussion and conclusions (Scottish Historical and Archaeological Internet Reports, 2010)
The fieldwork revealed just how widespread traces of past human activity are in the Buchan Valley. Most of the test-pit grids revealed lithic assemblages characteristic of prehistoric settlement-based activity from the Mesolithic to the Bronze Age. The extent of the work has been justified by recovery of nationally important lithic assemblages and by the recognition of changing procurement strategies over time in the Buchan Gravels.